Acacia dealbata invasion in Chile: Surprises from climatic niche and species distribution models. Issue 13 (23rd June 2019) - Langdon, Bárbara; Pauchard, Aníbal; Bustamante, Ramiro O.
Abstract: Aim: Tree invasions are a threat to biodiversity conservation, and although it is hard to predict the future spread of invasive tree species, there are tools available which could allow some estimations. The magnitude of spatial spread (a proxy of invasiveness) can be predicted from species climatic requirement (climatic niche) and can be represented by species distribution models (SDMs). We aimed to assess whether Acacia dealbata conserves its niche in the new environment of south‐central Chile, and also, to estimate the invasive stage of the species. Location: South‐central area of Chile, between the O'Higgins (34°0″0′S) and Aysen Regions (47°0″0′S). Methods: We used a combination of global, native, and regional data to improve the estimation of the potential distribution of A. dealbata, which has been considered one of the most invasive species of the genus, being registered in at least 34 countries in all the Continents. Results: Our results show that A. dealbata does not conserve its niche in the study area, invading areas with climatic conditions different from those of the native range. It is also not at equilibrium with the environment. According to the global versus regional SDM comparisons, populations present in south‐central Chile present different invasion stages. There are some stable populations, but there are other populations colonizing new areas, occupying unsuitable habitats and some of them are adapting to new climatic conditions. Climatic factors, such as precipitation seasonality, could be acting behind the expansion to new environments, and biotic factors or dispersal limitations could be preventing the species to colonize suitable areas. Main conclusions: The invasion process of A. dealbata is far from stabilizing, and management options should focus on prevention, avoiding, for example, the introduction of the species to Patagonia where the species has not spread yet. More research is needed to complement our results and enhance the development of effective management strategies. Abstract : Acacia dealbata invasive potential is widely known in several countries, including Chile. Using niche models based on native, global, and local occurrences, we determined locations are still available for the species to invade in south‐central Chile. Main management recommendation is to avoid the introduction of the species to Patagonia, where required climatic conditions are met.